2014
DOI: 10.1186/1749-7221-6-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of accessory deep peroneal nerve in referred patients to an electrodiagnostic medicine clinic

Abstract: BackgroundAccessory Deep Peroneal Nerve (ADPN) is an anatomic variation that can potentially cause disturbance in electrodiagnostic studies. This anomaly could be detected by nerve conduction studies. There are no recent updates about prevalence of this anatomic variation. Electrodiagnostic medicine clinic is the best environment for detecting presence and prevalence of this nerve, so present study enrolled.Materials & MethodsIn this cross sectional descriptive study that take place from March 2009 to July 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
2
6
0
Order By: Relevance
“…It was reported that ADPN was present in 12-35% of the popula- 58 . It was found that there is a wide variation of prevalence of ADPN among different studies [58][59][60][61][62][63] . One a meta-analysis study assessed the overall pooled ADPN prevalence of 18.8%, the electrophysiological pooled ADPN prevalence of 13.6%, and the anatomical pooled prevalence of 39.3% 63 .…”
Section: The Accessory Deep Peroneal Nervementioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that ADPN was present in 12-35% of the popula- 58 . It was found that there is a wide variation of prevalence of ADPN among different studies [58][59][60][61][62][63] . One a meta-analysis study assessed the overall pooled ADPN prevalence of 18.8%, the electrophysiological pooled ADPN prevalence of 13.6%, and the anatomical pooled prevalence of 39.3% 63 .…”
Section: The Accessory Deep Peroneal Nervementioning
confidence: 99%
“…Studying the ADPN can complicate the clinical picture and disturb the interpretation of the electrophysiological studies of common peroneal, deep peroneal, and superficial peroneal nerves lesions and injuries, as well as, ADPN neuropathy 54,57 . Namely, superficial peroneal nerve and its branches (including ADPN) are risk for iatrogenic damage while performing arthroscopy, local anesthetic block, surgical approach to the fibula, open reduction and internal fixation of lateral malleolar fractures, application of external fixators, elevation of a fasciocutaneous or fibular flaps for grafting, surgical decompression of neurovascular structures, or miscellaneous surgery on leg, foot and ankle 57,59 .…”
Section: The Accessory Deep Peroneal Nervementioning
confidence: 99%
“…The most prevalent anastomosis of lower limbs is additional deep fibular nerve (ADFN), which is formed from superficial peroneal nerve or its branch, which together with deep motor branch of common fibular nerve innervate flexor pedis and provides sensory innervation to the lateral part of the foot (Fig. 3) (34).…”
Section: Types Of Interneural Anastomoses Of Lower Limbsmentioning
confidence: 99%
“…Abnormalities of its components are useful in the diagnostic evaluation of neurological disorders ( fig 5). Special recording techniques are required when significantly different CMAP amplitude is recorded between two nerve segments in order to rule out the presence of anatomical variants [41][42][43][44].…”
Section: Emg Recording In Peripheral Nerve Stimulationmentioning
confidence: 99%